A bispecific antibody-drug conjugate targeting pCAD and CDH17 has antitumor activity and improved tumor-specificity - Alyssa Synan; Nila C. Wu; Roberto Velazquez; Thomas Gesner; Claude Logel; Kathrin Mueller; Andrew Green; Patrizia Barzaghi-Rinaudo; Quincey Simmons; Samuele Mercan; Xingyi Shi; Xun Li; et al. (mAbs)
P-cadherin (pCAD) and LI-cadherin (CDH17) are cell-surface proteins belonging to the cadherin superfamily that are both highly expressed in colorectal cancer. This co-expression profile presents a novel and attractive opportunity for a dual targeting approach using an antibody–drug conjugate (ADC). In this study, we used a unique avidity-driven in vitro screening approach to generate pCAD x CDH17 bispecific antibodies that selectively target cells expressing both antigens over cells expressing only pCAD or only CDH17. Based on in vitro binding and inhibition of cell proliferation results, we selected a lead bispecific antibody to link to the cytotoxic payload monomethyl auristatin E (MMAE) to generate a pCAD x CDH17 bispecific MMAE ADC. In in vivo dual flank mouse models, we demonstrated antitumor activity of the bispecific ADC in tumors expressing both antigens but not in tumors expressing only pCAD or only CDH17. Overall, the preclinical data presented here support the proof-of-concept bispecific antibody discovery approach, demonstrating a rational design for screening antibodies by prioritizing cross-arm avid IgGs to target dual-positive cells.